Mitigating Train Derailments Due to Sharp Curve and Overspeed - Sun, Yan Q. (Frontiers in Mechanical Engineering, 2018)
Each year around the world there are still several cases of train derailments on the curved tracks due to overspeed, leading to big casualties and costs to the rail industries. With the ongoing increase on the speed, the possibility of train derailment increases, especially on the sharp curved tracks. Guard rails are usually placed parallel to regular running rails along areas of restrictive clearance, such as a bridge, tunnel, or sharp curved track. They have the effect of keeping the wheels of rolling stock in alignment in case of derailment. The investigation on the guide rail which is used to mitigate the train derailment due to a curved track and overspeed is carried out through the simulations. The simulation results show that installing guard rails can largely reduce the train derailment potential caused by a sharp curve and overspeed. The clearance between the low rail and the guard rail (namely, the flangeway width) is critical for the effectiveness of guard rail. The optimal position of guide rail – the height over the top of low railhead and lateral distance between guide rail and low rail would be determined through the simulations.